Nitric Oxide and Reactive Oxygen Species Mediate Metabolic Changes in Barley Seed Embryo during Germination - Ma, Zhenguo; Marsolais, Frédéric; Bykova, Natalia V.; Igamberdiev, Abir U. (Frontiers in Plant Science, 2016)
The levels of nitric oxide (NO) and reactive oxygen species (ROS), ATP/ADP ratios, reduction levels of ascorbate and glutathione, expression of the genes encoding proteins involved in metabolism of NO and activities of the enzymes involved in fermentation and in metabolism of NO and ROS were studied in the embryos of germinating seeds of two barley (Hordeum vulgare L.) cultivars differing in dormancy level. The level of NO production continuously increased after imbibition while the level of nitrosylated SH-groups in proteins increased. This corresponded to the decrease of free SH-groups in proteins. At early stage of germination (0-48 h postimbibition) the genes encoding class 1 phytoglobin (the protein scavenging NO) and S-nitrosoglutathione reductase (scavenging S-nitrosoglutathione) were markedly expressed. More dormant cultivar exhibited lower ATP/ADP and ascorbate/dehydroascorbate ratios and lower lactate and alcohol dehydrogenase activities, while the production of NO and nitrosylation of proteins was higher as compared to the non-dormant cultivar. The obtained data indicate that at the onset of germination NO is actively generated causing nitrosylation of SH-groups and a switch from respiration to fermentation. After radicle protrusion the metabolism changes in a more reducing type as recorded by ratio of reduced and oxidized glutathione and ascorbate. The turnover of NO by the scavenging systems (phytoglobin, S-nitrosoglutathione reductase and interaction with ROS) might contribute to the maintenance of redox and energy balance of germinating seeds and lead to alleviation of dormancy.